Boosting research momentum: thesis boot camp for DBA students 2023 - Abdullah, Johari; Chung, Ellen; Nik Fauzi, Sheela Faizura (UiTM Sarawak, 2024)
The highly anticipated Thesis Boot Camp for DBA Students 2023 organised by the Centre of Graduate Studies (CGS), UiTM Cawangan Sarawak took place on June 10 and 11. UiTM. This immersive event brought together twelve (12) Doctor of Business Administration (DBA) candidates to foster a conducive environment for research and progress in their doctoral journey, especially to prepare for their upcoming Defence of Research Proposal (DRP).